Role of the Legislature in Budget Processes - Lienert, Ian. (Washington, D.C. : International Monetary Fund, 2010)
This paper examines the role of the legislature in budget processes. The paper highlights that for promoting good governance and fiscal transparency, the legislature's active engagement in the budget process is essential. When fiscal policies and medium-term budgetary objectives are debated in parliament, budget strategies and policies are 'owned' more widely. However, more active participation by the legislature runs the risk that fiscal discipline deteriorates. In countries where the legislature has unrestrained budget amendment authority, parliament is prone to introduce changes that increase spending or reduce taxes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet